"Plastic ocean": What about cancer?. (December 2015) - Erren, Thomas C.; Groß, J. Valérie; Steffany, Frank; Meyer-Rochow, V. Benno
Abstract : Marine plastic pollution may contribute to wildlife and human cancer.